Towards the DSM-6: results of a survey of experts on the reintroduction of first-rank symptoms as core criteria of schizophrenia and on redefining hallucinations - Moritz, Steffen; Borgmann, Lisa; Heinz, Andreas; Fuchs, Thomas; Gallinat, Jürgen (Schizophrenia bulletin, 2024)
Diagnostic criteria for mental disorders are subject to change. This is particularly true for schizophrenia, whose diagnostic criteria in the current DSM-5 bear little resemblance to what Kraepelin once named “dementia praecox” and Bleuler termed “the schizophrenias.” The present study reports results from a survey of experts on two core topics of schizophrenia: (a) whether subsequent editions of the DSM should once again give the Schneiderian first-rank symptoms (FRS; eg, thought broadcasting) the prominent role they had in the DSM-IV and (b) whether the currently quite narrow definition of hallucinations in the DSM-5 requiring them to be vivid and clear and have the full force and impact of normal perceptions should be broadened to incorporate perceptual-like phenomena that the individual can differentiate from proper perceptions but still perceives as real and externally generated.The aim of the survey was to learn about experts’ opinions with no clear hypotheses.International experts on schizophrenia were recruited via various sources and invited to participate in a short online survey. The final sample comprised 136 experts with a subgroup of 53 experts with verified identity and at least 6 years of clinical and/or research experience.Slightly more experts voted in favor (49.3%) of returning FRS to the prominent role they had in earlier versions of the DSM than against (34.6%). Approximately four out of five experts agreed that the definition of hallucinations in the DSM should be expanded. According to the results, alongside internal symptoms that are phenomenologically indistinguishable from true perceptions, sensory intrusions that the holder is convinced were inserted from another source (ie, not self-generated) should be included in the definition.While a large majority of experts recommend a change in the definition of hallucinations, the experts’ opinions on FRS are more mixed. We hope that this article will stimulate future studies targeting the diagnostic relevance of these symptoms and encourage discussion about the definition of core psychotic symptoms and the diagnostic criteria for the upcoming edition of the DSM.
Gesehen am 14.11.2024